Genetic diversity of Dioctophyme renale in Southern South America - Arce, Lucas F. (2024)
Dioctophyme renale, the giant kidney worm, is a nematode related to Trichuris sp and is distributed worldwide. These parasites locate in the kidney of their definitive hosts (mainly belonging to the order Carnivora) and have an indirect life cycle with an annelid as the main intermediate host. Humans are rarely affected, but in those that are, 1 or both kidneys are destroyed. In South America, D. renale is widespread in riparian regions where changing climatic conditions, environmental degradation, and compromised sanitation are increasing the risk of distribution of this parasite, including humans. Here, we provide the descriptions of the genetic diversity of the parasite in the region by analysing 73 adult D. renale samples collected from domestic and wild carnivores. The most common hosts were (Canis lupus familiaris) and maned wolf (Chrysocyon brachyurus Fam. Canidae) among domestic and wild carnivores, respectively. This work shows the descriptions of the genetic diversity of this parasite complementing molecular methods and classical and probabilistic phylogeography. Our results strongly suggest that this parasite has been present on the continent long enough to develop local genetic variants. Also, the phylogenies show transmission between localities and bidirectional transmission between domestic and wild species. We now have new tools to understand the ecological dynamics of this parasite such as molecular markers to study its genetic diversity as well as for identification and reporting in cryptic cases.